A Review of Torque Ripple Reduction Techniques in Switched Reluctance Motors - Vaibhav Godase; Swapnil Takale; Rahul Ghodake (International Journal of Electrical Machine Analysis and Design, 2025)
Switched Reluctance Motors (SRMs) have emerged as a promising alternative to conventional motor technologies due to their rugged structure, low manufacturing cost, high-temperature capability, and suitability for harsh environments. Despite these advantages, the widespread adoption of SRMs in applications such as electric vehicles, household appliances, industrial drives, and aerospace systems is significantly restricted by the issue of torque ripple. Torque ripple manifests as periodic fluctuations in the developed electromagnetic torque, primarily arising from the motor’s doubly salient geometry, nonlinear magnetic characteristics, and discrete phase commutation. These fluctuations not only reduce the mechanical performance of the drive system but also increase acoustic noise, vibration, and component wear, thereby compromising overall system efficiency and user comfort. This review paper provides a comprehensive examination of the major torque ripple reduction techniques proposed in recent literature. The discussion covers structural design improvements, advanced control strategies, current profiling methods, converter-based enhancements, and emerging hybrid intelligent approaches. Each category is analyzed with respect to its operating principle, effectiveness, practical limitations, and applicability to modern SRM systems. The review highlights that while design-based solutions offer inherent improvements, control-oriented and intelligent techniques provide greater adaptability and superior dynamic performance. However, no single method offers a universal solution, underscoring the need for integrated approaches that combine machine design optimization, intelligent torque control, and advanced power electronics. The paper concludes by identifying key research challenges and outlining future directions aimed at enabling SRMs to achieve smoother torque production suitable for next-generation high-performance applications.
Keywords: Switched reluctance motor; acoustic noise; current profiling; torque ripple; torque sharing function